Pengaruh Motivasi Kerja, Komunikasi dan Stres Kerja terhadap Kepuasan Kerja karyawan pada PT. X cabang kota Malang - Jayanti Khusnul Kholifah; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrack This study aims to determine the effect of work motivation, communication, and job stress on employee job satisfaction at PT. X Malang City Branch. The sample used in this study were 43 employees. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Testing the data used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the variables of work motivation, communication, and job stress had a positive and significant effect on job satisfaction of PT. X Malang City Branch and based on the results of a partial test (t test) the variable of work motivation has a positive and significant effect on job satisfaction of employees of PT. X Malang City Branch, the communication variable has a positive and significant effect on job satisfaction of PT. X Malang City Branch and work stress variables have no significant effect on job satisfaction of employees of PT. X Malang City Branch. Keywords : Work Motivation, Communication, Job Stress And Job Satisfaction.